Mortality in a Heterogeneous Population of Low-Risk Febrile Neutropenic Patients Treated Initially with Cefazolin and Tobramycin - Francesca Le Piane; Sandra AN Walker; Scott E Walker; Nina Lathia; Carlo De Angelis; Andrew Simor (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: At Sunnybrook Health Sciences Centre in Toronto, Ontario, the recommended empiric regimen for febrile neutropenia has been cefazolin and tobramycin for at least 25 years. However, we had no objective data to reassure us that patient mortality had not increased over the past five years.